2017
DOI: 10.1186/s40942-017-0075-x
|View full text |Cite|
|
Sign up to set email alerts
|

pH of anti-VEGF agents in the human vitreous: low impact of very different formulations

Abstract: Background The aim of the study was to measure pH changes of the human vitreous caused by the intravitreal drugs bevacizumab, ranibizumab, aflibercept, and ziv-aflibercept.MethodsFresh human vitreous samples were obtained during core vitrectomy (23-gauge) from patients with epiretinal gliosis. Aliquots of bevacizumab, ranibizumab, aflibercept or ziv-aflibercept (2 µl) were added consecutively to 200 µl of vitreous samples or 0.9% NaCl saline. The pH was measured using a pH-sensitive microelectrode. Rituximab, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…We included histidine chloride pH 5.5 buffer as a control since clinical tolerability data can be cross-referenced for this formulation. 2 Here we show that all buffers in the pH 4.0 to 5.5 range were well tolerated and did not cause inflammation, intraocular pressure (IOP) changes, or gross or microscopic findings in any eye.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…We included histidine chloride pH 5.5 buffer as a control since clinical tolerability data can be cross-referenced for this formulation. 2 Here we show that all buffers in the pH 4.0 to 5.5 range were well tolerated and did not cause inflammation, intraocular pressure (IOP) changes, or gross or microscopic findings in any eye.…”
Section: Introductionmentioning
confidence: 83%
“…The current nonclinical and clinical data suggest that pH 5.5 to 7.4 is an acceptable range for intravitreally administered drugs. 1,2 The pH of the drug product is an important manufacturability parameter as it generally affects drug properties as well as shelf life. It is desirable to avoid extreme pH conditions and formulate drugs close to the physiological vitreous pH in order to limit the disruption of the ocular environment.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, GPC peaks and PDI for both copolymers 1 and 2 (1.22 and 1.36) showed low polydispersity, uniformity and a unimodal distribution. One important aspect in the development of preparations for intravitreal administration is the resultant pH, in order to avoid any harmful effects due to pH deviation from physiological values [ 40 ]. Some studies have previously described the use of different aqueous vehicles like acetate buffer [ 41 ], water [ 42 ] or sodium chloride (NaCl) to prepare PLGA-PEG-PLGA based hydrogel formulations.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that this pH difference is easily buffered by the vitreous after intravitreal injection. [26] Furthermore, the retina has no nociceptor and sensory innervation to feel the pain related to pH changes. [27] The pain felt during injection is thought to be felt through scleral sensory nerves.…”
Section: Discussionmentioning
confidence: 99%